2001
DOI: 10.1046/j.0953-816x.2001.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic kynurenate‐sensitive receptors inhibit glutamate release

Abstract: Kynurenic acid is a tryptophan metabolite provided with antagonist activity on ionotropic glutamate and alpha7 nicotinic acetylcholine receptors. We noticed that in rats with a dialysis probe placed in the head of their caudate nuclei, local administration of kynurenic acid (30-100 nM) significantly reduced glutamate output. Qualitatively and quantitatively similar effects were observed after systemic administration of kynurenine hydroxylase inhibitors, a procedure able to increase brain kynurenate concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(160 citation statements)
references
References 47 publications
(63 reference statements)
9
147
0
4
Order By: Relevance
“…These results, taken together, demonstrate that up-and downregulation of endogenous KYNA in the brain acutely modulate hippocampal chemistry and function in vivo. Our findings confirm and extend reports of similar glutamate changes following KYNA manipulations in other forebrain regions (Carpenedo et al, 2001;Konradsson-Geuken et al, 2009;Wu et al, 2010), and are also in line with experiments showing cognitive impairments following systemic administration of kynurenine, the immediate bioprecursor of KYNA (Chess and Bucci, 2006;Chess et al, 2007;Erhardt et al, 2004;Shepard et al, 2003). Most importantly, the present data provide the first demonstration that the cognitive improvement seen in animals with genetic, that is, chronic, elimination of KAT-II (Potter et al, 2010) can be duplicated by acute, specific KAT-II inhibition.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results, taken together, demonstrate that up-and downregulation of endogenous KYNA in the brain acutely modulate hippocampal chemistry and function in vivo. Our findings confirm and extend reports of similar glutamate changes following KYNA manipulations in other forebrain regions (Carpenedo et al, 2001;Konradsson-Geuken et al, 2009;Wu et al, 2010), and are also in line with experiments showing cognitive impairments following systemic administration of kynurenine, the immediate bioprecursor of KYNA (Chess and Bucci, 2006;Chess et al, 2007;Erhardt et al, 2004;Shepard et al, 2003). Most importantly, the present data provide the first demonstration that the cognitive improvement seen in animals with genetic, that is, chronic, elimination of KAT-II (Potter et al, 2010) can be duplicated by acute, specific KAT-II inhibition.…”
Section: Discussionsupporting
confidence: 80%
“…Microdialysis studies in the striatum and the prefrontal cortex of awake rats showed that exogenous application of KYNA in the mid-nanomolar range, that is, 2-5 times endogenous levels, reduces the extracellular concentrations of dopamine and glutamate (Amori et al, 2009;Carpenedo et al, 2001;Moroni et al, 2005;Rassoulpour et al, 2005;Wu et al, 2010). Moreover, in the prefrontal cortex, nanomolar KYNA significantly decreases the amphetamine-induced stimulation of acetylcholine release (Zmarowski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the affinity of KYNA to these two Ca 2ϩ -permeable receptors is in the range of KYNA levels in the human brain and reasonably close to the (lower) KYNA content of the rodent brain suggests a physiological function in glutamatergic and cholinergic neurotransmission. Direct support for such a role has been provided, for example, by in vivo studies in the rat striatum where a reduction in KYNA levels enhances vulnerability to an excitotoxic insult (Poeggeler et al, 1998) and, conversely, modest elevations of KYNA inhibit glutamate release (Carpenedo et al, 2001). …”
Section: Neuroactive Tryptophan Metabolitesmentioning
confidence: 99%
“…Inhibition of these receptors by KYNA reduces extracellular glutamate levels (Carpenedo et al, 2001;Rassoulpour et al, 2005;Grilli et al, 2006). Preliminary evidence indicates that reductions in KYNA, conversely, enhance glutamatergic function by disinhibiting α7nAChRs (H.-Q.…”
Section: Discussionmentioning
confidence: 99%
“…These glia-derived signals or "gliotransmitters" include, among others, D-serine (Schell, 2004;Nishikawa, 2005;Martineau et al, 2006) and the tryptophan metabolite kynurenic acid (KYNA; Kiss et al, 2003). The latter compound is especially interesting, because it not only inhibits the NMDA receptor directly by acting at the glycine co-agonist ("glycine B ") site (Kessler et al, 1989;Parsons et al, 1997) but also decreases extracellular glutamate levels by blocking presynaptic α7 nicotinic receptors (α7nAChRs) situated on glutamatergic nerve endings (Carpenedo et al, 2001;Rassoulpour et al, 2005). KYNA is therefore increasingly viewed as an important endogenous modulator of physiological and pathological events associated with glutamatergic neurotransmission (Schwarcz, 2004;Coyle, 2006).…”
mentioning
confidence: 99%